Réponses

Meilleure réponse !
2014-04-04T19:18:56+02:00
1) A = 4x²-(x-3)(x-2)+2(x-2)
       = 4x²-(x²-2x-3x+6)+2x-4
       = 4x²-x²+2x+3x-6+2x-4
       = 3x²+7x-10

2) pour x=-5
A = 3×(-5)²+7×(-5)-10
   = 3×25-35-10
   = 30

pour x=1/2
A = 3×(1/2)²+7×1/2-10
   = 3×1/4+7/2-10
   = 3/2+7/2-10
   = 10/2-10
   = 5-10
   = -5
Merci beaucoup ! :)
Es-tu sur que c'est ça ? :D
A part une éventuelle erreur de calcul, oui ^^
D'accord merci beaucoup ! :S
De rien !
2014-04-04T19:36:17+02:00
1) A = 4x²-(x-3)(x-2)+2(x-2)
       = 4x²-(x²-2x-3x+6)+2x-4
       = 4x²-x²+2x+3x-6+2x-4
       = 3x²+7x-10

2) pour x=-5
A = 3×(-5)²+7×(-5)-10
   = 3×25-35-10
   = 30

pour x=1/2
A = 3×(1/2)²+7×1/2-10
   = 3×1/4+7/2-10
   = 3/2+7/2-10
   = 10/2-10
   = 5-10
   = -5